Headgroup Effects on the Unusual Lamellar-Lamellar Coexistence and Vesicle-to-Micelle Transition of Salt-Free Catanionic Amphiphiles - Silvas, BFB (2010)
Salt-free ion-paired catanionic amphiphiles of the C(m)(+) C(n)(-) type, with a high solubility mismatch (n >> m or m >> n) display a remarkable phase behavior in water. A temperature-driven vesicle-to-micelle transition in the dilute side together with a coexistence of two lamellar phases oil the concentrated side is one of the peculiar effects that have been reported for the hexadecyltrimethylammonium octylsulfonate surfactant, C(16)C(8) or TA(16)So(8) (extensive to C(14)C(8) and C(12)C(8)). In this work, with TA(16)So(8) as a reference, the cationic trimethylammonium (TA(+)) and pyridinium (P(+)) headgroups are combined with the anionic sulfate (S(-)) and sulfonate (So(-)) headgroups to yield other C(16)C(8) compounds: hexadecyltrimethylammonium octylsulfate (TA(16)S(8)) 1-hexadecylpyridinium octylsulfonate (P(16)So(8)), and 1-hexadecylpyridinium octylsulfate (P(16)So(8)). We show that, if the asymmetry of the chain lengths is kept constant at C(16)C(8) and the headgroup chemistry is changed, most of the unusual self-assembly properties are still observed, indicating that they are not system-specific but extensive to other combinations of headgroups and mainly dictated by the ion-pair solubility mismatch. Thus, all the compounds in water quite remarkably show a lamellar-lamellar phase coexistence and spontaneously form vesicles upon solubilization. Moreover, P(16)So(8) undergoes at temperature-driven vesicle-to-micelle transition that involves an intermediate planar lamellar state, similar to TA(16)So(8). Some interesting effects on the global phase behavior, however, do arise when the headgroups are changed, Geometric packing effects are shown to be important, but the differences in phase behavior seem to be mainly dictated by (i) the charge density of the headgroups, which tunes the solubility mismatch of the ion-pair, and (ii) specific interactions between headgroups, which affect the short-range repulsive force that controls the swelling of the concentrated lamellar phase,